Case report: Early-onset parkinsonism among the neurological features in children with PHACTR1 variants - Previtali, Roberto; Leidi, Alessia; Basso, Martina; Izzo, Giana; Stignani, Cecilia; Spaccini, Luigina; Iascone, Maria; Veggiotti, Pierangelo; Bova, Stefania Maria (Frontiers in Neurology, 2023)
PACHTR1 is expressed in cardiovascular and neurological tissues. In the brain, it has a role in pre- and post-natal maturation. Previously reported PHACTR1-mutated patients showed early-onset epilepsy and intellectual disability. We describe two unreported cases with de novo pathogenic variants in PHACTR1 and their clinical pictures, compared with those of cases already reported in the literature. In line with previous reports, the two patients presented early-onset developmental and epileptic encephalopathy. In addition, one patient developed a speech disorder and a progressive movement disorder characterized by hypertonus, hypo-bradykinesia, hypomimia, ataxic gait, and retropulsion. She was treated with levodopa without any clinical improvement. Pathogenic variants in PHACTR1 may result in a cardiological or neurological phenotype. Severe developmental delay, intellectual disability, and early-onset developmental and epileptic encephalopathy are the main features of PHACTR1-mutated patients with neurological involvement. Movement and speech disorders have never previously been described and could be new features of the neurological phenotype.